Quantitative MRI in post-operative paediatric cerebellar mutism syndrome. Issue 108 (November 2018) - Toescu, Sebastian M.; Hales, Patrick W.; Aquilina, Kristian; Clark, Chris A.
Highlights: Post-operative paediatric cerebellar mutism syndrome is a well-recognised complication of posterior fossa tumour surgery. Diffusion tractography shows damage to cerebellar outflow pathways are implicated in the development of pCMS. Perfusion imaging has shown widespread bloodflow deficits in patients with pCMS, which reverses when symptoms improve. Timely application of diffusion and perfusion MRI studies may help us to answer several remaining questions in pCMS. Abstract: Post-operative paediatric cerebellar mutism syndrome (pCMS) occurs in around 25% of children undergoing surgery for cerebellar and fourth ventricular tumours. Reversible mutism is the hallmark of a syndrome which comprises severe motor, cognitive and linguistic deficits. Recent evidence from advanced neuroimaging studies has led to the current theoretical understanding of the condition as a form of diaschisis contingent on damage to efferent cerebellar circuitry. Tractography data derived from diffusion MRI studies have shown disruption of the dentato-rubro-thalamo-cortical tract in patients with pCMS, and perfusion studies have indicated widespread supratentorial regions which may give rise to the florid signs and symptoms of pCMS. Given the difficulties in predicting pCMS from standard structural MRI, this review discusses findings from quantitative MRI modalities which have contributed to our understanding of this debilitating syndrome, and considers the goals and challenges which lie ahead in the field.